The partisan effects of voter turnout: How conservatives profit from rainy election days - Felix Arnold; Ronny Freier (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
In this short note, we use data from different elections in the German state of North-Rhine Westphalia between 1975 and 2010 to show that the social democrats generally profit from higher voter turnout at the expense of the conservatives. We deal with the endogeneity of voter turnout by using election day rain as an instrumental variable. Our particular contribution is the comparison of municipal and state elections.
Keywords: D72; H70; 330; Turnout; Partisan Effects; Rain; Germany; Municipalities; Elections